Pengaruh Pemberian Ekstrak Etanol Daun Pepaya Jepang (Cnidoscolus aconitifolius (Mill.) I.M. Johnst) Terhadap Diferensial Leukosit Mencit Putih Jantan - Relin Yesika; Irmisya Nure Firania; Fauzia Noprima Okta; Aina Fatkhil Haque; Rizki Oktarini; Yogie Andika Tri Nanda; Elisa Ayudia (LPPM Universitas Abdurrab, 2024)
Immunomodulators are medicines that alter or influence the immune system to make it work more effectively. Immunomodulators can increase (immunostimulants) or decrease immune response (immunosuppressants). Secondary metabolites that have immunomodulatory activity are polyphenols, alkaloids, and terpenoids. One of the plants that contain these secondary metabolites is Japanese papaya leaves. Japanese papaya leaves have been widely used as traditional medicine to treat various diseases. This study aims to determine the effect of the administration of Japanese papaya leaf extract on differential leukocytes of male white mice. This study used 24 male white mice with skin allergies after administering 20% ovalbumin 0.2 mL/20g BW intraperitoneally on day 1 and day 7 subcutaneously. Twenty male white mice were divided into 4 groups. Group I (control) mice weren’t given ovalbumin antigen or papaya leaf extract; groups II, III, and IV were given ovalbumin and extract (100; 200; 400 mg/kg BW). After oral administration of the extract for seven days, leukocyte differential count of white mice. Giving ethanol extract of japanese papaya leaves at doses of 100, 200, and 400 mg/kg BW can significantly affect leukocyte differentials, namely lymphocytes and monocytes (p<0.05). While basophils, eosinophils, rod-neutrophils, and segment-neutrophils are not significantly different (p>0.05).